Estudo da evolução de cloretos no processo de destilação de petróleo - Chimin, Roberta Quintino Frinhani (2013)
During oil refining, the equipment is constantly exposed to the action of compounds such as salts, organic and inorganic acids, sulfides, and carbonates among others, which lead to decrease in equipment service life. The presence of these contaminants bring many challenges, requiring actions of refiners to avoid problems such as corrosion,fouling problemsandreductionthe effectiveness of catalysts. Among the contaminants, the salts, as the chlorides of sodium, calcium and magnesium,are among the most common.Reducing salt in oil is essential to avoid the presence of mainly chlorides in the overhead systemsat refineries.The chlorides, especially calcium and magnesium undergo hydrolysis in the presence of water and temperatures around 250 °C. These conditions are common in refining environments and the result of this hydrolysis process is the formation and the possible accumulation of hydrochloric acid in water in the overhead systemsof the towers refining.Atrefineries,themixtures containing oils various types of oil, especially those arising from new fields,are carefully treated to avoid high chlorides contents in the overhead systems. This study propose at investigating the release process of chlorides by developing a method that allows assessing, comparing, and monitoring the hydrochloric acid generated during oil distillation in order to foresee oil behavior duringrefining and propose strategies to reduce operating costs of oil refining.For this study, six samples of different oils were distilled. The methodology involved in adapting a glassware specific system in column top of the distillation unit oil, located in LabPetro / UFES in order to monitor and capture the hydrochloric acid generated.Salinity mass data balance were obtained, as well as their respective chloride release percentage, during the distillation process, in other words, the amount of chloride inthe initial sample disengaged during the distillation process.The results show that the methodology is efficient because the data obtained from the salinity mass balance showed low losses and the replicates carried out were very similar. The correlationsbetween the release percentage of chlorides and their counterions reveal satisfactory results.